De Olympische spelen van 1928 . The Olympic Games 1928 - Perel, Jules (Netherlands Filmmuseum, 2008)
Amsterdam hosted the Olympic Games from May 17 to August 12, made possible thanks to public support as the Queen of the Netherlands Wilhelmine was against the event, considering it a "demonstration of paganism". For the first time the Olympic flame lit up the stadium night and day but Queen Wilhelmine refused to attend the opening ceremony. The 9th Olympiad in Amsterdam was noted not only for the appearance of the olympic flame, but for the appearance of women in athletics events (100m, 800m, 4x100m relay, the high jump and the discus) - despite recommendations to the contrary by Baron de Coubertin. Germany returned to Olympic competition at the 1928 Games, which featured the debut of the Olympic flame. Approximately 3,000 athletes (including nearly 300 women), representing 46 countries, participated in the Olympics.